Teknologi Branding dalam Pengemasan Produk Emping Melinjo Upaya Meningkatkan Partisipasi, Keterampilan dan Pemasaran Masyarakat Pedesaan di Desa Mancak, Kecamatan Mancak Kabupaten Serang - Edy Nasri (ABDIKARYA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2020)
The purpose of the Student Work Lecture Community Service Program is as Learning and Empowerment for the Community in order to improve skills and help increase sales of products produced by the Village community. The products produced by the special community of Mancak Village are emping melinjo is a typical and iconic product of tourism in Serang Regency as the village center of emping melinjo. The problem faced is that the production processing is still done traditionally and attractive packaging has not been made and the customer is still doing it by selling to middlemen / collectors. as a result, the marketed production is still small and the attributes of the melinjo chips product are still simple, there are not many variations, causing a low selling value. The method that is used to develop this community service implementation is through (1) Survey through observation, interviews, and analysis of problems and village potentials, (2) Graphic Design Training, (3) packaging manufacturing training using branding technology. From the results of implementation through community service programs, the increase in community knowledge and skills regarding (1) Utilizing multimedia, and (2) making packaging with branding technology. In this activity, it is expected to increase knowledge and skills in branding technology for packaging processing